How to Achieve Further Progress of Journal of Korean Neurosurgical Society (JKNS) - Improve the Impact Factor (IF) and Maintain It Continuously - Hee-Jin Yang (Journal of Korean Neurosurgical Society, 2024)
Journal of Korean Neurosurgical Society (JKNS), which has a history of over 50 years, has made great progress recently. In order to continue this progress in the future, we need to think about the strategies we will take and put them into practice. The progress of JKNS is an important opportunity to publicize the achievements of Korean neurosurgery to the world and for Korea to contribute further to global neurosurgery. We also need to think about and implement various measures to improve the inflow of papers of high quality from various countries and to establish an appropriate merit system for reviewers.